Business groups in the West : origins, evolution, and resilience - Colpan, Asli M.; Hikino, Takashi (Oxford : Oxford University Press, 2018)
This volume aims to explore the long-term evolution of different varieties of large enterprises in today's developed economies. It focuses on the economic institution of business groups and attempts to comprehend the factors behind their rise, growth, struggle, and resilience; their behavioral and organizational characteristics; and their roles in national economic development. The volume seeks to enhance the scholarly and policy-oriented understanding of business groups in developed economies by bringing together state-of-the-art research on the characteristics and contributions of large enterprises in an evolutionary perspective. While business groups are a dominant and critical organization model in contemporary emerging economies and have lately attracted much attention in academic circles and business presses, their counterparts in developed economies have not been systematically examined. This book aims to fill this gap in the literature and is the first scholarly attempt to explore the evolutional paths and contemporary roles of business groups in developed economies from an internationally comparative perspective. In doing so, it argues that business groups actually rose to function as a critical factor of industrial dynamics in the context of Second Industrial Revolution in the late nineteenth century. They have adapted their characteristic roles and transformed to fit to the changing market and institutional settings. As they flexibly co-evolve with the environment, the volume shows that business groups can remain as a viable organization model in the world's most advanced economies today.
Publikace se zaměřuje na dlouhodobý vývoj podnikatelských skupin ve vyspělých ekonomikách a analyzuje jejich vznik, růst, adaptaci i odolnost vůči ekonomickým změnám. Autoři sledují, jak tyto skupiny formovaly národní hospodářství, jaké měly organizační a behaviorální rysy a jak se přizpůsobovaly proměnlivým tržním a institucionálním podmínkám. Kniha zdůrazňuje, že podnikatelské skupiny sehrály zásadní úlohu již od druhé průmyslové revoluce koncem 19. století a zůstávají životaschopným organizačním modelem i v dnešních vyspělých ekonomikách. Z mezinárodně srovnávacího hlediska publikace doplňuje chybějící výzkum o roli velkých podniků v rozvinutých zemích a přináší nové poznatky pro ekonomickou teorii i hospodářskou politiku.
Obsahuje bibliografické odkazy a rejstřík
Keywords: 19.-21. století; podnikatelské sítě; kooperace podniků; strategické aliance; mezinárodní podnikání; vyspělé země; srovnávací studie; 19th-21st centuries; business networks; cooperation of business enterprises; strategic alliances (business); international business; developed countries; comparative studies